2019
DOI: 10.1186/s13071-019-3574-9
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of an iron-inducible Haemaphysalis longicornis tick-derived promoter in an Ixodes scapularis-derived tick cell line (ISE6)

Abstract: Background Ticks are important vectors of disease-causing pathogens. With the rise of resistance to chemical acaricides, alternative methods in tick control are warranted. Gene manipulation has been successful in controlling mosquitoes and mosquito-borne diseases and is now looked upon as a candidate method to control ticks and tick-borne pathogens. Our previous study has identified the actin and ferritin promoter regions in the H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…(D) The Dsor1 3’UTR was cloned in the pmirGLO/Fer-Luc2/Act-hRluc vector [51], and ISE6 cells that were soaked with the indicated dsRNA were transfected with the sensor plasmid. The ratio between firefly luc and Rluc was normalized to that of the empty sensor, and the means and standard deviations are shown in the chart (n=7).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…(D) The Dsor1 3’UTR was cloned in the pmirGLO/Fer-Luc2/Act-hRluc vector [51], and ISE6 cells that were soaked with the indicated dsRNA were transfected with the sensor plasmid. The ratio between firefly luc and Rluc was normalized to that of the empty sensor, and the means and standard deviations are shown in the chart (n=7).…”
Section: Resultsmentioning
confidence: 99%
“…A statistically significant increase in the IscDsor1 level was also observed upon Ago-96 knockdown, in addition to RdRP1 knockdown, suggesting that Ago-96 might also be involved in the regulation of IscDsor1 (Figure 7C). To test if RdRP1 regulates IscDsor1 through its 3'UTR, we cloned IscDsor1 3'UTR after the firefly luciferase coding region of the pmirGLO/Fer-Luc2/Act-hRluc vector (54). After depleting RdRP1 or RdRP3 in ISE6 cells, we transfected the IscDsor1 3'UTR sensor plasmid and performed dual luciferase assays to detect up-regulation of sensors upon knockdown of RdRPs (Figure 7D).…”
Section: Misregulation Of the Gene Dsor1 Homolog (Isci005428 Hereafter Iscdsor1) Uponmentioning
confidence: 99%
See 1 more Smart Citation
“…They showed that silencing of FER1 expression by RNA interference led to a decrease in ISE6 cell proliferation and an increase in mortality, concluding that ISE6 cells could be a good tool to further understanding of the mechanism of FER1 action. Thereafter, Hernandez et al (2019) characterized the activity of an iron-inducible tick promoter derived from the tick Haemaphysalis longicornis, previously identified by Kusakisako et al (2018b), in ISE6 cells, which could be a valuable tool in the development of a gene-manipulation system to control ticks and TBPs. Kusakisako et al (2018a) established methods to visualize H 2 O 2 in ISE6 cells using an intracellular H 2 O 2 probe and observed that paraquat, known to induce oxidative stress in mammalian cells (Table 2), was also effective in this respect in ISE6 tick cells.…”
Section: Tick Cell Lines Elucidate Novel Aspects Of Tick Cell Metabolmentioning
confidence: 99%
“…Kusakisako et al (2018a) established methods to visualize H 2 O 2 in ISE6 cells using an intracellular H 2 O 2 probe and observed that paraquat, known to induce oxidative stress in mammalian cells (Table 2), was also effective in this respect in ISE6 tick cells. Iron derived from host blood may react with oxygen in the tick's body and lead to high levels of H 2 O 2 , causing oxidative stress such as DNA strand breaks, lipid peroxidation and degradation of other molecules (Kusakisako et al, 2018a;Hernandez et al, 2019).…”
Section: Tick Cell Lines Elucidate Novel Aspects Of Tick Cell Metabolmentioning
confidence: 99%